Apresiasi Sastra Siswa Sekolah Dasar di Kota Sorong: Literary Appreciation of Elementary School Students in Sorong City - Muntihanah Muntihanah (Balai Bahasa Provinsi Papua, 2020)
This paper aims to measure appreciation level of Grade V students in Sorong toward literature. This measurement uses penilaian acuan kriteria (PAK) approach beside Direct Evaluation of Literature and Indirect Evaluation of Literature. The result shows that on the whole appreciation level of literature of the Grade V students in Sorong Municipality is in Kurang with mean score 54.64. Particularly, Indirect Appreciation Level of Literature got much lower score by mean score 37.13. Meanwhile, Direct Appreciation Level got better level with predicate Satisfatory by mean score 62.77.